Renaissance man: Hugh Grant's performance of class, white Englishness, and joyfully mature masculinity. Issue 1 (2nd January 2023) - Hallet, Marion
ABSTRACT: Hugh Grant's career and persona have undergone a cultural, personal, and professional shift since the 2010s. During a period of semi-hiatus from acting, Grant became associated with politics as he campaigned for the protection of privacy and opposed Brexit. At the same time, his image has been reshaped through fatherhood, often depicted by the press as the reason behind his 'comeback'. Since Florence Foster Jenkins in 2016, he has turned towards more 'serious' roles and distanced himself from his romcom persona. Focusing on his most recent roles in film and television, this article analyses the star's performances and dissects the ambiguities and tensions at play in Grant's ageing white 'English' upper-class image. Although inextricably associated with the romantic genre for years, I suggest that Grant's acting style and persona are more in a state of perpetual flux, attached to the past yet increasingly layered with enjoyment for the craft as he ages. At the intersection of gender, ageing and star studies, this article shows how an ageing persona is (re-)established on screen, and how Grant's characters within his films and television series might render a different image of white, privileged, English masculinity in contemporary times.